1985
DOI: 10.1002/jmv.1890170210
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of hepatitis A on a hospital ward

Abstract: An outbreak of hepatitis A has been recognised on a medical ward of a district general hospital. Eleven nurses and one patient were reported to have hepatitis over a period of 18 days in October, 1984. Specific tests for hepatitis A IgM were positive in all cases. Following extensive investigations, the outbreak was traced to a female patient who had recently returned from India and who was incontinent. Her serum, when tested subsequently, showed evidence of recent hepatitis A infection. The implications of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…The mean age of the students was 21 ± 2 years (range [17][18][19][20][21][22][23][24][25][26][27]. Most of the students (n = 132, 53.4%) were from the western parts of Turkey.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age of the students was 21 ± 2 years (range [17][18][19][20][21][22][23][24][25][26][27]. Most of the students (n = 132, 53.4%) were from the western parts of Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of HAV outbreaks have been reported in paediatric or neonatal intensive care units, but some outbreaks have also been reported from general wards [20]. Outbreaks are often related to breakdowns in infection control procedures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The transmission of other infections through fecal exposure, and the occurrence of nosocomial outbreaks of HAV due to orofecal transmission [Ebisawa, 1984;Klein et al, 1984;Skidmore et al, 1985;Drusin et al, 1987] underline the need for good fecal hygiene in hospitals [Sepkowitz, 1996]. This is particularly important for HAV, as the virus remains infectious for a long time at room temperature [McCaustland et al, 1982].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of nosocomial outbreaks due to HAV transmission from patients to nurses [Goodman et al, 1982;Klein et al, 1984;Skidmore et al, 1985;Drusin et al, 1987] and vice versa [Ebisawa, 1984] is well documented. Foodborne outbreaks [Meyers et al, 1975] have also been reported in the hospital setting.…”
Section: Introductionmentioning
confidence: 99%